Method for preparing sodium alginate silicon dioxide core-shell microspheres by template method and application of sodium alginate silicon dioxide core-shell microspheres

The formation of silica shell on the surface of sodium alginate microspheres by template method is solved, and the problem of uneven microsphere size in traditional methods is realized, and the preparation of sodium alginate/silica core-shell structure microspheres of different sizes is realized and Excellent adsorption performance.

CN119406375AActive Publication Date: 2025-02-11NORTHWEST UNIVERSITY FOR NATIONALITIES
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411617248.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-11
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The traditional preparation method for sodium alginate/silica microspheres cannot accurately control the particle size of the microspheres, resulting in uneven size distribution, limiting the research and application of its adsorption properties.

Method used

Using the template method, a silica shell was generated on the surface of sodium alginate microspheres through TEOS hydrolysis and polycondensation reaction between silicon hydroxyl groups, thereby achieving the preparation of sodium alginate/silica core-shell structure microspheres of different sizes.

Benefits of technology

Accurate control of microsphere sizes is achieved, and its adsorption performance is enhanced, and it is particularly suitable for water treatment and gas purification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a method for preparing sodium alginate / silicon dioxide core-shell microspheres by a template method, which comprises the following steps: (1) preparing sodium alginate microspheres: preparing sodium alginate microspheres with different sizes as template cores coated by a silicon dioxide layer according to the required size by using a microsphere preparation instrument, and preparing the sodium alginate microspheres by using a template method; and (2) coating of a silicon dioxide shell layer: putting the sodium alginate microspheres in the step (1) into an aqueous solution containing tetraethoxysilane (TEOS), and carrying out in-situ polymerization on the surfaces of the sodium alginate microspheres through hydrolysis and self polycondensation of the TEOS to generate the silicon dioxide layer so as to obtain the sodium alginate / silicon dioxide core-shell structure microspheres with different sizes. The method does not depend on ethanol catalysis in the preparation process, so that the condensation reaction between silicon hydroxyl and hydroxyl in sodium alginate is weakened, a silicon dioxide coating is formed through the hydrolysis effect of TEOS in a water phase system and polycondensation between silicon hydroxyl, the surface of the sodium alginate microsphere is coated with the silicon dioxide coating, and the surface of the sodium alginate microsphere is coated with the silicon dioxide coating. Controllable preparation of sodium alginate / silicon dioxide core-shell microspheres of different sizes can be achieved, and in addition, the influence of the sizes of the core-shell structure microspheres on the adsorption performance of the microspheres is further studied.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing sodium alginate / silicon dioxide core-shell microspheres by a template method, and belongs to the fields of material chemistry and nanotechnology. Background Art

[0002] Sodium alginate / silica composite microspheres (SA@SiO2) have become an important material in the fields of environmental governance, gas purification and water treatment due to their excellent adsorption properties and broad application prospects. However, there are some limitations in the traditional preparation method of SA@SiO2 microspheres. The traditional preparation method involves mixing sodium alginate solution with TEOS, ethanol and ammonia solution, and then curing it by extrusion into a calcium chloride solution to form composite microspheres. This method is simple and easy to implement, but it has some obvious disadvantages. First, it cannot accurately control the particle size of the microspheres, resulting in uneven size distribution of the obtained microspheres. Secondly, due to the lack of precise control of the size of the microspheres, it is difficult to study the specific effect of size on the adsorption performance of SA@SiO2, which limits its application.

[0003] Furthermore, in the preparation of SA / SiO2 core-shell structured microspheres, the condensation reaction between tetramethoxysilane in ethanol solution and the hydroxyl group of sodium alginate was utilized to prepare a composite microsphere structure with silica embedded in the surface of the sodium alginate microspheres (Roosen, J., et al. Industrial&Engineering Chemistry Research, 54(51), 12836-12846.), which improved the strength of the sodium alginate microspheres, but failed to achieve the preparation of multi-sized SA / SiO2 core-shell structures.

[0004] Therefore, a new preparation method was developed to prepare core-shell composite microspheres through a template method to achieve precise control of the size of SA / SiO2 microspheres. At the same time, the hydrogel properties of sodium alginate were combined to achieve rapid swelling of the microspheres and enhance their adsorption performance, which is of great significance for improving their application in environmental governance. Summary of the invention

[0005] The purpose of the present invention is to provide a new method for preparing sodium alginate / silicon dioxide core-shell microspheres (SA / SiO2) by a template method, which overcomes the limitation of the traditional method that the size of the composite microspheres cannot be accurately controlled by ethanol-catalyzed condensation of silanol and sodium alginate hydroxyl groups.

[0006] The present invention generates a silica shell layer on the surface of a sodium alginate microsphere by TEOS hydrolysis and polycondensation reaction between silanol groups, thereby obtaining sodium alginate / silicon dioxide core-shell structure microspheres of different sizes. The preparation of the core-shell microspheres is achieved in two steps: (1) firstly, sodium alginate microspheres of different sizes are prepared as templates by a microsphere preparation instrument; (2) sodium alginate microspheres of different sizes are placed in TEOS, water and ammonia water, and the silica shell layer is polymerized on the surface of the sodium alginate microsphere template by TEOS hydrolysis and polycondensation between silanol groups. During the preparation process, the size of the composite microspheres is further controlled by the reaction time of sodium alginate and TEOS aqueous solution and the concentration of TEOS. The prepared sodium alginate / silicon dioxide core-shell microspheres can achieve efficient adsorption of tetracycline pollutants.

[0007] The present invention uses a sodium alginate solution of a certain concentration as a raw material, and uses a microsphere preparation instrument to quickly prepare sodium alginate microspheres of different sizes (120 μm, 150 μm, 200 μm, 450 μm, 300 μm, and 750 μm). 2+ The cross-linking reaction is solidified and stable, and TEOS is further used as a silicon source to quickly form a silica shell layer (30 minutes) on the surface of the sodium alginate microspheres through hydrolysis and polycondensation, thereby realizing the preparation of size-controllable SA / SiO2 core-shell structure microspheres. Specifically, the following steps are included: (1) Prepare a sodium alginate aqueous solution with a mass fraction of 0.5-1.5%, and remove bubbles by ultrasonication; (2) placing the prepared sodium alginate solution in a solution bottle, connecting the solution bottle to a microsphere preparation instrument, and preparing sodium alginate microsphere cores of different sizes as templates; the particle size of the sodium alginate microsphere template is 120-750 μm; The parameters of the microsphere preparation instrument are: nozzle particle size: 120~750 μm, Frequency: 170~1500, Electrode: 250V, Pressure: 270~600 mbar, Heating: 60 ℃; (3) adding the prepared sodium alginate microspheres into a CaCl2 solution with a mass concentration of 2-4% and stirring at room temperature for 10-50 min to obtain solidified and stable sodium alginate microspheres; (4) adding tetraethoxysilane (TEOS), water, and ammonia water to the sodium alginate microspheres in (3), reacting at room temperature for 10 to 50 min, collecting the microspheres, and freeze-drying to obtain sodium alginate / silica core-shell microspheres; The mass ratio of sodium alginate microspheres to TEOS is 5:1~268:1; the mass ratio of sodium alginate microspheres to water is 2.5:1~2.5:1.5; the mass ratio of sodium alginate microspheres to ammonia water is 14:1~9:1. Freeze drying is performed at -45~-25 ℃ for 24~48 h. The schematic diagram of the preparation process is shown in Figure 1 shown.

[0008] The invention prepares SA / SiO2 core-shell structure microspheres with good biocompatibility and mechanical stability by controlling the size of sodium alginate microspheres and the coating thickness of silicon dioxide. The method comprises the following steps: (1) preparation of sodium alginate microspheres: using a microsphere preparation instrument, according to the required size, preparing sodium alginate microspheres of different sizes as templates for subsequent silicon dioxide layer coating, (2) coating of the silicon dioxide layer: placing the sodium alginate microspheres in step (1) in a reaction solution containing tetraethoxysilane (TEOS), and generating a silicon dioxide layer on the surface of the sodium alginate microspheres by hydrolysis and self-condensation of TEOS, thereby obtaining sodium alginate / silicon dioxide core-shell structure microspheres of different sizes. Compared with other sodium alginate / silica microsphere preparation methods, this method does not rely on ethanol catalysis during the preparation process, thereby weakening the condensation reaction between silanol and hydroxyl in sodium alginate, and forms a silica coating through TEOS hydrolysis and condensation between silanol itself, which is coated on the surface of sodium alginate microspheres, thereby realizing the controllable preparation of SA / SiO2 core-shell microspheres of different sizes. In addition, the present invention also studies the effect of size on adsorption performance, further broadening its application prospects in sewage treatment, air purification, biological drug delivery and other fields.

[0009] In summary, the novel method for preparing SA / SiO2 core-shell microspheres by a template method provided by the present invention not only prepares SA / SiO2 core-shell microspheres of different sizes, but also has excellent adsorption performance, and is particularly suitable for fields such as water treatment and gas purification. By adjusting the amount of TEOS, reaction time, etc., the size and adsorption performance of SA / SiO2 microspheres can be further optimized to achieve efficient adsorption of different pollutants. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 Schematic diagram of the preparation of sodium alginate / silicon dioxide (SA / SiO2) core-shell microspheres of different sizes in the present invention.

[0011] Figure 2 The actual pictures and SEM characterization results of SA / SiO2 core-shell microspheres of different sizes prepared in Example 1.

[0012] Figure 3 The actual pictures and SEM characterization results of SA / SiO2 core-shell microspheres of different sizes prepared in Example 2.

[0013] Figure 4 This is a physical picture of SA / SiO2 core-shell microspheres of different sizes prepared in Example 3.

[0014] Figure 5 This is a physical picture of the SA / SiO2 core-shell microspheres prepared in Example 4.

[0015] Figure 6 The actual picture and SEM characterization results of SA / SiO2 core-shell microspheres prepared in Example 5.

[0016] Figure 7 The experimental results of tetracycline (TC) adsorption on SA / SiO2 core-shell microspheres of different sizes. DETAILED DESCRIPTION

[0017] The following uses tetracycline as an adsorption marker and further illustrates the template preparation and adsorption capacity of SA / SiO2 core-shell microspheres in conjunction with the accompanying drawings.

[0018] Example 1 This embodiment provides a new method for preparing SA / SiO2 core-shell microspheres by template method, which is as follows: (1) Prepare 1% sodium alginate solution and remove bubbles by ultrasonication; (2) placing the prepared sodium alginate solution in a solution bottle, connecting the solution bottle to a microsphere preparation instrument, and the instrument parameters are: nozzle particle size: 750 μm, Frequency: 220, Electrode: 250 V, Pressure: 170 mbar, Heating: 60°C; preparing a sodium alginate microsphere template; (3) The sodium alginate microspheres prepared under the parameters set in (2) were stirred in a 3% CaCl2 solution for 30 min; (4) 2.5 g (wet weight) of sodium alginate microspheres prepared in (3) were placed in a round-bottom flask, 30 μL of TEOS, 1 mL of water, and 200 μL of ammonia water were added to the flask, and the mixture was reacted at room temperature for 30 min. The mixture was freeze-dried at -40 °C for 48 h to obtain SA / SiO2-750. Figure 2 (A, B) are the physical picture and SEM picture of SA / SiO2-750 respectively. The particle size of the prepared SA / SiO2-750 is about 1.2 mm; the SEM results show that on the basis of the original SA core template, silica successfully forms a shell structure on its surface, increasing the size of the original core, and the surface has a certain degree of roughness.

[0019] Example 2 This embodiment provides a method for preparing sodium alginate / silica core-shell microspheres by a template method. The preparation process is different from that in Example 1 in that the parameters of the microsphere preparation instrument are: nozzle particle size: 450 μm, Frequency: 270, Electrode: 250 V, Pressure: 270 mbar, Heating: 60°C; the other steps are the same as in Example 1 to obtain SA@SiO2-450.

[0020] Figure 3 The actual picture and SEM picture of SA / SiO2-450 prepared in Example 2. The particle size of the prepared SA@SiO2-450 is about 1 mm. The SEM results show that based on the original SA core template, silica successfully forms a shell structure on its surface, which increases the size of the original core and has a certain degree of roughness.

[0021] Example 3 This embodiment provides a method for preparing SA / SiO2 core-shell microspheres by a template method. The preparation process is different from that of Example 1 in that the parameters of the microsphere preparation instrument are as follows: the nozzle particle sizes are 300 μm, 200 μm, 150 μm, and 120 μm, respectively, Frequency: 470, Pressure: 300 mbar, Heating: 60°C; the other steps are the same as those in Example 1, and SA@SiO2-300, SA@SiO2-200, SA@SiO2-150, and SA@SiO2-120 are obtained.

[0022] Figure 4 Physical pictures of SA / SiO2-300, SA / SiO2-200, SA / SiO2-150, and SA / SiO2-120 prepared in Example 3.

[0023] Example 4 This embodiment provides a method for preparing sodium alginate / silicon dioxide core-shell microspheres by a template method. The preparation process is different from that of Example 1 in that the amounts of TEOS used are 100 μL and 500 μL, respectively, and the other steps are the same as those in Example 1.

[0024] Figure 5 The actual pictures are of SA / SiO2-750-100 and SA / SiO2-750-500 prepared in Example 4. As can be seen from the figure, SA / SiO2 core-shell microspheres of different sizes can be prepared by changing the amount of TEOS.

[0025] Example 5 This example provides a method for removing sodium alginate by calcination to obtain a silicon dioxide empty shell structure, which further proves that TEOS is coated on the surface of sodium alginate by forming a silicon dioxide shell layer. The preparation process is: placing the prepared SA / SiO2-750 in a tube furnace, heating to 600°C and calcining for 30 minutes.

[0026] Figure 6 The actual picture and SEM characterization result picture of SiO2 prepared in Example 5 show that after calcination to remove the sodium alginate core, the outer layer is indeed a spherical silica shell structure, which verifies the effectiveness of the template method.

[0027] Taking tetracycline (TC) as the target pollutant, the relationship between the size and adsorption performance of the core-shell structure SA / SiO2 was studied as follows: (1) Take 2 mg of each SA / SiO2 core-shell microsphere sample in Examples 1-3; (2) Prepare a 100 mg / L tetracycline (TC) solution; (3) The SA / SiO2 sample was added to TC, and an adsorption experiment was performed using a magnetic stirrer at a rotation speed of 200 rpm. The adsorption amount of TC by SA / SiO2 was then calculated and the adsorption capacity was recorded.

[0028] Figure 7 This is the adsorption effect diagram of SA@SiO2 of different sizes on 100mg / LTC. Figure 7 The adsorption experimental results show that the adsorption capacity of SA / SiO2-750 for TC in Example 1 is 486.47 mg / g; the adsorption capacity of SA / SiO2-450 for TC in Example 2 is 413.66 mg / g; the adsorption capacity of SA / SiO2-300 for TC in Example 3 is 301.73 mg / g, the adsorption capacity of SA / SiO2-200 for TC is 293.58 mg / g, the adsorption capacity of SA / SiO2-150 for TC is 190.89 mg / g, and the adsorption capacity of SA@SiO2-120 for TC is 133.84 mg / g; as the size decreases, the adsorption performance decreases.

Claims

1. A method for preparing sodium alginate / silicon dioxide core-shell microspheres by a template method, comprising the following steps: (1) Prepare a sodium alginate aqueous solution with a mass fraction of 0.5-1.5%, and remove bubbles by ultrasonication; (2) placing the prepared sodium alginate aqueous solution in a solution bottle, connecting the solution bottle to a microsphere preparation instrument, and dropping into a calcium chloride solution to prepare sodium alginate microspheres; the particle size of the sodium alginate microspheres is 120-750 μm; (3) adding the sodium alginate microspheres into a CaCl2 solution with a mass concentration of 2-4% and stirring at room temperature for 10-50 min to obtain solidified and stable sodium alginate microspheres; (4) Tetraethoxysilane, water, and ammonia water are added to the solidified and stabilized sodium alginate microspheres, and the reaction is carried out at room temperature for 10 to 50 minutes to obtain sodium alginate / silica core-shell microspheres, which are then freeze-dried to obtain dry microspheres.

2. The method for preparing sodium alginate / silicon dioxide core-shell microspheres by template method according to claim 1, characterized in that: The parameters of the microsphere preparation instrument are: nozzle particle size: 120~750μm, Frequency: 170~1500, Electrode: 250 V, Pressure: 270~600 mbar, Heating: 60℃.

3. The method for preparing sodium alginate / silicon dioxide core-shell microspheres by template method according to claim 1, characterized in that: The mass ratio of sodium alginate microspheres to TEOS is 5:1~268:1; the mass ratio of sodium alginate microspheres to water is 2.5:1~2.5:1.5; the mass ratio of sodium alginate microspheres to ammonia water is 14:1~9:

1.

4. The method for preparing sodium alginate / silicon dioxide core-shell microspheres by template method according to claim 1, characterized in that: Freeze drying is the process of freeze drying at -45~-25 ℃ for 24~48 hours.

5. Use of sodium alginate / silicon dioxide core-shell microspheres prepared according to the method of claim 1 as an adsorbent in tetracycline adsorption.

Citation Information

Patent Citations

  • Preparation and application for nanometer SiO2 strengthened calcium alginate-xanthan gum composite absorbent

    CN102671641A

  • Preparation method of oxidized graphene and sodium alginate composite absorbing material capable of removing ciprofloxacin in aqueous solution

    CN105536726A

  • Preparation method of porous calcium alginate gel spheres for treating heavy metal sewage

    CN109364887A

  • Preparation method of bioreactor with magnetic core-shell structure

    CN117563563A